Literatura devota em Portugal no tempo dos Filipes : o Memorial da Infância de Cristo, de Soror Maria de Mesquita Pimentel - Morujão, Isabel (1998)
The comparison between the heroic verses of this Cistercian nun, the Meditações da Vida de Cristo (for many years attributed to St Boaventura) and the Exercícios Espirituais, from St Ignatius, helped us to establish, on the one hand, the importance of these two works on the spiritual development of the Portuguese members of female religious Orders, and on the birth of some of the 17th Century conventual women’s literature, on the other hand, in a period in which Portugal was still dominated by the Spanish rule of the Filipes.